Dendrimers: Analytical characterization and applications - Biricova, V; Laznickova, A (Bioorganic chemistry, 2009)
This review focuses on analytical techniques used for separation and characterization of dendrimers and their derivatives. These macromolecules have been attractive material for a development of new drug carriers and imaging agents. They are also interesting for many biological and industrial applications. The review mentions a few of them.
Keywords: nosiče léků; polypropyleny; Drug Carriers; kontrastní látky; Dendrimers; Polypropylenes; polyaminy; chemické techniky analytické; Chemistry Techniques, Analytical; Polyamines; dendrimery; Contrast Media